In vitro Regeneration of two BINA Tomato (Lycopersicon esculentum Mill.) Varieties of Bangladesh (Plant Tissue Culture and Biotechnology, 2022)
Cotyledonary leaf from 12 days old aseptically grown seedlings were used as explant. Cotyledonary leaf explants of two BINA varieties of tomato were cultured on MS medium containing different concentrations and combinations of BAP, Kn and IAA for multiple shoot formation via organogenesis. 100% shoot induction was observed when the explants were cultured on MS medium supplemented with BAP, Kn and IAA. Earliest shoot induction was observed within four weeks. The MS media supplemented with 1.5 mg/l BAP + 0.5 mg/l Kn + 0.2 mg/l IAA found to be the best medium with regards to number of days required for the initiation of regeneration, no. of multiple shoot formation and regeneration frequency in case of both the varieties. Shoot elongation was obtained in the same regeneration medium. The elongated shoots were rooted on half strength MS medium supplanted with 0.2 mg/l IBA. The in vitro rooted plantlets were successfully established in soil with 97% survival rate. Subsequently, the plantlets were transferred to large earthen pot for acclimatization and finally, transferred to the open field for further growth and development.Plant Tissue Cult. & Biotech. 32(1): 43-51, 2022 (June)